Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan PT. Bekaert Indonesia (Studi Kasus Operator Produksi PCR1) - Iskandar, Fikri; Triana, N. Neni; Nadeak, Thomas (Peneliti.net, 2024)
The COVID-19 pandemic has had a significant impact on the quality of work in Indonesia. This study is to see both factors of the work environment and compensation whether it can improve the performance of employees of PT Bekaert Indonesia. This study uses descriptive quantitative research methods to examine the effect of work environment and compensation on employee performance of PT Bekaert Indonesia. The research population is the company's production employees. The sample was selected using the accidental method of 68 respondents, using a questionnaire with a Likert scale to collect data. Data analysis using multiple linear regression after fulfilling the classical assumption test and validity and reliability tests. Based on the results of the study, it can be concluded that the work environment and compensation affect employee performance. The majority of PT Bekaert Indonesia employees show moderate performance. The work environment of PT Bekaert Indonesia is mostly moderate. Similarly, the majority of PT. Bekaert Indonesia's compensation is at a moderate level. Research shows that the work environment and compensation partially and simultaneously have a significant effect on employee performance. The work environment and compensation are factors in influencing employee performance at PT. Bekaert Indonesia by 42.2%.